Spectroscopic characterization of a coumarin-labelled therapeutic tetrapeptide - Santos, F. C. (2015)
The present work describes the synthesis of the tetrapeptide H-Ala-Ala-Pro-Val-NH2 (AAPV), an important inhibitor of the enzyme human neutrophil elastase, labelled at the C-terminus with a 7-methoxycoumarinyl moiety. Photophysical studies were made with spectroscopic characterization by UV-vis and fluorescence spectroscopy in different organic solvents and mixtures with aqueous HEPES solution, in order to simulate physiological conditions.